Overview of Stunting Data and Special Nutrition Interventions In Bungo Regency, Jambi Province - Sari, Rini Maya; Sunarsih, Elvi; Mufazoh; Liveona, Nise (PT. Hafasy Dwi Nawasena, 2024)
The problem of stunting in children under five is a major concern in global public health. Stunting, which is caused by chronic malnutrition, is a serious problem with nearly 200 million children under the age of five experiencing it worldwide. This condition not only affects children's physical growth, but also impacts their cognitive development and long-term health. This report uses descriptive analytical research methods to assess the situation of stunting, specifically in Bungo District.The results of the situation analysis in Bungo District show that there are 25 villages that are the locus of stunting with high prevalence rates of stunted children under five. This shows that the problem of stunting in this region really needs special attention and more intensive handling. Interventions that have been carried out in Bungo District include various efforts, such as providing nutritious supplementary food, increasing access to health services, and educating pregnant and lactating mothers about the i The conclusions from this study emphasize the importance of focusing on specific areas to address stunting in Bungo District. To reduce stunting rates, innovative specific intervention efforts in nutrition are needed. These could include programs that support improving children's nutritional intake, improving the quality of water and sanitation, and monitoring children's growth regularly. With an integrated approach and focus on the specific needs of each region, it is hoped that the stunting rate in Bungo District can be significantly reduced, so that children can grow and develop optimally.mportance of balanced nutrition.